MANIPULATIVE TECHNOLOGIES IN ELECTORAL PROCESSES: CONTENT AND COUNTERACTION METHODS - Takhmina Mamadaliyeva (Web of Journals Publishing, 2025)
This article examines manipulative technologies in the electoral sphere as a set of methods used to influence voters and distort election outcomes. It emphasizes their role in creating a pseudo-reality and reinforcing dominant ideologies. Particular attention is paid to transitional societies, such as Uzbekistan, where democratic institutions are still in development. The study analyzes the essence, forms of electoral manipulation and offers recommendations to counteract these practices in the interests of information security and political system stability.
Keywords: Electoral manipulation, political culture, information security, transitional society, Uzbekistan, ideology, voter consciousness.